Enacting quality improvement in ten European hospitals: a dualities approach - Nunes, F. G.; Robert, G. B.; Weggelaar, A. -M.; Wiig, S.; Aase, K.; Karltun, A.; Fulop, N. J. (BMC Health Services Research, 2020)
Background: Hospitals undertake numerous initiatives searching to improve the quality of care they provide, but these efforts are often disappointing. Current models guiding improvement tend to undervalue the tensional nature of hospitals. Applying a dualities approach that is sensitive to tensions inherent to hospitals’ quest for improved quality, this article aims to identify which organizational dualities managers should particularly pay attention to. Methods: A set of cross-national, multi-level case studies was conducted involving 383 semi-structured interviews and 803 hours of non-participant observation of key meetings and shadowing of staff in ten purposively sampled hospitals in five European countries (England, the Netherlands, Portugal, Sweden, and Norway). Results: Six dualities that describe the quest for improved quality, each embracing a seemingly contradictory feature were identified: plural consensus, distributed connectedness, orchestrated emergence, formalized fluidity, patient coreness, and cautious generativeness. Conclusions: We advocate for a move from the usual sequential and project-based and systemic thinking about quality improvement to the development of meta-capabilities to balance the simultaneous operation of opposing ideas or concepts. Doing so will help hospital managers to deal with major challenges of change inherent to quality improvement initiatives.